Edukacja prawna w szkołach ponadpodstawowych - Wilk, Anna (Studia Edukacyjne, 2024)
The article addresses the issue of legal education in secondary schools, especially in the context of recent changes that drastically reduce the legal issues discussed in the core curriculum. The author presents the social importance of legal education and the need to raise legal awareness, compares the past and current scope of law-related content provided in the subjects “Social Knowledge” and “History and the Present”, and formulates postulates as to the future form of education law in secondary schools.